Is the Urine Cannabinoid Level Measured via a Commercial Point-of-Care Semiquantitative Immunoassay a Cannabis Withdrawal Syndrome Severity Predictor? - Claus, Benedikt Bernd; Specka, Michael; McAnally, Heath; Scherbaum, Norbert; Schifano, Fabrizio; Bonnet, Udo (Frontiers in Psychiatry, 2020)
Background: For cannabis-dependent subjects, the relationship between the cannabis withdrawal syndrome (CWS) severity and the related urine cannabinoid concentration is unclear; focus was here on the use of a commercial point-of-care (POC) enzyme-immunoassay detecting 11-nor-9-carboxy-Delta9-tetrahydrocannabinol (THC-COOH). Methods: Observational study of 78 adult chronic cannabis-dependent subjects assessed over a 24-day, and 13 serial measurement-days, inpatient detoxification-treatment. Repeated Measures Correlation and Multilevel Linear Models were here considered. Results: THC-COOH levels significantly correlated with Marihuana-Withdrawal-Checklist (MWC) scores across the whole study (r = .248, p < .001). Correlation between serial creatinine-adjusted THC-COOH ratios and serial MWC-scores emerged as significant only in the sample with higher MWC scores (>11 points) at admission (n=21, r = .247, p = .002). MWC scores were significantly correlated with the Clinical-Global-Impression-Rating-Severity (CGI-S; r = .812, p < .001). Females showed a significantly slower decline in urine THC-COOH levels and prolonged CWS course characterized by substantial illness-severity (according to CGI-S), occurring in nearly 30% of cases. Conclusions: Urine cannabinoid levels (THC-COOH) determined by POC-assay significantly, but mildly to moderately, predicted CWS severity hence helping in defining the duration of detoxification treatment. In patients with >11-point MWC at admission, creatinine-adjusted THC-COOH ratios significantly, and mildly to moderately, predicted CWS-severity. Females showed prolonged withdrawal levels.